DC: Reinforcement Learning for Context-aware and Adaptive Lighting Design using Extended Reality: Impacts on Human Emotions and Behaviors - Mohammadrezaei, Elham (2024 IEEE Conference on Virtual Reality and 3D User Interfaces Abstracts and Workshops (VRW), 2024)
In the interconnected world of smart built environments, Extended Reality (XR) emerges as a transformative technology that can enhance user experiences through personalized lighting systems. The integration of XR with deep reinforcement learning for adaptive lighting design (ALD) has potential to optimize visual experiences while addressing real-time data analysis, XR system complexities, and integration challenges with building automation systems. The research centers on developing an XR-based ALD system that dynamically responds to user preferences, thereby positively impacting human emotions, behaviors, and overall well-being.